Distinct surface response to black carbon aerosols - T. Tang; D. Shindell; Y. Zhang; A. Voulgarakis; A. Voulgarakis; J.-F. Lamarque; G. Myhre; G. Faluvegi; G. Faluvegi; B. H. Samset; T. Andrews; D. Olivié; et al. (Atmospheric Chemistry and Physics, 2021)
For the radiative impact of individual climate forcings, most previous studies focused on the global mean values at the top of the atmosphere (TOA), and less attention has been paid to surface processes, especially for black carbon (BC) aerosols. In this study, the surface radiative responses to five different forcing agents were analyzed by using idealized model simulations. Our analyses reveal that for greenhouse gases, solar irradiance, and scattering aerosols, the surface temperature changes are mainly dictated by the changes of surface radiative heating, but for BC, surface energy redistribution between different components plays a more crucial role. Globally, when a unit BC forcing is imposed at TOA, the net shortwave radiation at the surface decreases by -5.87±0.67<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="64pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="ceddc505c45ef5b5f6c3122544bef0be"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-13797-2021-ie00001.svg" width="64pt" height="10pt" src="acp-21-13797-2021-ie00001.png"/></svg:svg> W m−2 (W m−2)−1 (averaged over global land without Antarctica), which is partially offset by increased downward longwave radiation (2.32±0.38 W m−2 (W m−2)−1 from the warmer atmosphere, causing a net decrease in the incoming downward surface radiation of -3.56±0.60<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="64pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="bc04927f65185fee6e3bc79d26026e88"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-13797-2021-ie00002.svg" width="64pt" height="10pt" src="acp-21-13797-2021-ie00002.png"/></svg:svg> W m−2 (W m−2)−1. Despite a reduction in the downward radiation energy, the surface air temperature still increases by 0.25±0.08 K because of less efficient energy dissipation, manifested by reduced surface sensible (-2.88±0.43<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="64pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="17d6b80fda128263ff2096d02e99a496"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-13797-2021-ie00003.svg" width="64pt" height="10pt" src="acp-21-13797-2021-ie00003.png"/></svg:svg> W m−2 (W m−2)−1) and latent heat flux (-1.54±0.27<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="64pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="6b74b260ecb790dac717b7f5288056b6"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-13797-2021-ie00004.svg" width="64pt" height="10pt" src="acp-21-13797-2021-ie00004.png"/></svg:svg> W m−2 (W m−2)−1), as well as a decrease in Bowen ratio (-0.20±0.07<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="64pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="b5dff9acfed0d4a91c65237a7a1d1703"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-13797-2021-ie00005.svg" width="64pt" height="10pt" src="acp-21-13797-2021-ie00005.png"/></svg:svg> (W m−2)−1). Such reductions of turbulent fluxes can be largely explained by enhanced air stability (0.07±0.02 K (W m−2)−1), measured as the difference of the potential temperature between 925 hPa and surface, and reduced surface wind speed (-0.05±0.01<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="64pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="dacbece38c26a62ebd66aa672dc3d356"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-13797-2021-ie00006.svg" width="64pt" height="10pt" src="acp-21-13797-2021-ie00006.png"/></svg:svg> m s−1 (W m−2)−1). The enhanced stability is due to the faster atmospheric warming relative to the surface, whereas the reduced wind speed can be partially explained by enhanced stability and reduced Equator-to-pole atmospheric temperature gradient. These rapid adjustments under BC forcing occur in the lower atmosphere and propagate downward to influence the surface energy redistribution and thus surface temperature response, which is not observed under greenhouse gases or scattering aerosols. Our study provides new insights into the impact of absorbing aerosols on surface energy balance and surface temperature response.